PERLAKUAN AKUNTANSI PENDAPATAN DAN PENYAJIANNYA DALAM KEWAJARAN LAPORAN KEUANGAN PADA PT. ANDOWA NATHA WISTARA - Budi Tri Rahardjo, Ak., M.Ak., CA; Rosmawati Rosmawati (Program Studi Magister Manajemen Universitas Krisnadwipayana, 2019)
This research was based on the results of the discussion that has been done by the researcher, it can be concluded the recognition and measurement of income at PT. Andowa Natha Wistara is in conformity with Statement of Financial Accounting Standards No.23. Where the recognition of corporate income using the accrual basis method of income is recognized at the time of the transaction of the sale of services by the company. Recognition of revenues has been referred to in the Statement of Financial Accounting Standard No.23 in terms of the sale value of services recorded as such income can be estimated with certainty and most likely to be realized. Measurement of income uses the historical measurement basis based on the fair value of benefits received or to be received in cash and cash equivalents.